Viability of subscriber operated prepaid cell phone loading station using technology foresight scenario building - Ortiz, Glenn N. (University of the Philippines Diliman, 2011)
The proponent decided to study the "viability of subscriber operated prepaid cell phone loading station using technology foresights: scenario building" as the special project in TM 299. The project participants of this exercise are the Electronics and Communication Engineers, Electronics Faculty of TUP-Taguig, Electronics and Communication Engineering Students of TUP-Taguig, Electronics Technician Working in Analog Devices Philippines and Loading Retailers. The issue of this study is to commercialize and determine the market and service viability for the subscriber operated prepaid cell phone loading station. STEEP analysis, SWOT analysis, forum, financial presentation and surveys are the tools employed to analyze the commercialization of the project. The proponent used the 10 steps in scenario building exercise and come up with three major scenarios. The assessment of these scenarios will be the guide of the stakeholders for the commercialization of the subscribers operated prepaid cell phone loading station. Technology Road Mapping for this study is also given for proper implementation of the subscriber operated prepaid cell phone loading station.